Investigation of Phase Transformation of Fe65Ni35 Alloy by the Modified Pulse Method - Janusz Terpiłowski (Materials, 2020)
This paper presents the possibility of using a modified-pulse method (MPM) determining the temperature characteristics of thermal diffusivity in order to identify phase transformations in metals. The experiment and attempt of phase identification were conducted for the Fe65Ni35 alloy in the 20–500 °C temperature range during both sample heating and cooling. The estimated error of discrete thermal diffusivity measurements was less than 3%. The method allows us to narrow down the averaging of the interval of this value, as a function of temperature, in the range below 1 K. Recently published analysis of the phase diagrams of Fe–Ni alloys, and the results of the authors’ own research into the Fe65Ni35 alloy, showed very good correlation between changes occurring when heating the alloy and the equilibrium diagram provided by Cacciamani G., Dinsdale A., Palumbo M., and Pasturel A. (Intermetallics 18, 2010, 1148–1162) showing the position of phases with a crystal-lattice structure based on the face-centered cubic (FCC) cell.